Signaling properties of Ascaris motorneurons: graded active responses, graded synaptic transmission, and tonic transmitter release - Davis, RE (J Neurosci, 1989)
The commissural motorneurons of the nematode Ascaris are capable of transmitting signals passively over long distances with little decrement. This ability is due to the high resistivities of their membranes (Davis and Stretton, 1989). Although these cells rely on their passive properties for long-distance signaling, voltage-sensitive channels are present in commissural membranes. These channels underlie the graded active responses that can be elicited at the offset of abrupt hyperpolarizing and depolarizing intracellular current pulses. The inhibitory motorneurons generate membrane potential oscillations when they are strongly depolarized. All-or-none action potentials have never been observed to occur spontaneously, nor has it been possible to evoke them even when the cells have been strongly hyperpolarized to remove any possible channel inactivation. Our findings indicate that the typical all-or-none action potentials so commonly used in nerve cells throughout the animal kingdom do not occur in these cells. Synaptic transmission is therefore mediated without spikes and is graded. The resting potentials of Ascaris motorneurons lie where the synaptic input-output curves are steepest, above the threshold for release of neurotransmitter. Tonic transmitter release from commissural motorneurons may be the neural mechanism underlying the hydrostatic skeleton of Ascaris.